Second-Wave Effects of Covid’19 Pandemic on Transportation Business: Keke-Napep and Motor-Cycle Transport Systems in Asaba Metropolis, Nigeria - Edih University O; Faghawari Nyanayon D (Rowter Journal, 2023)
Transnational, global trades, investments, travels amongst other drivers of globalization helped to reverberate the deadly coronavirus pandemic from Wuhan, China across the world like whirl fire. In order to contain the infectious spread of the pandemic and mitigate its negative effects on macro-economic variables, World Health Organization, WHO designed Covid-19 protocols that are being enforced by governments and people of the world. It is on this account that the study examined the Second wave effect of Covid’19 pandemic on transportation business: Keke-Napep and Motor-cycle transport systems in Asaba metropolis, Nigeria. The main objective is to determine empirically the real impact of the pandemic on rural land transport business. The study employed structured questionnaire and interview methods to generated data from the 250 respondents selected using census sampling technique. Out of the 250 sets of questionnaire administered, 235 (94%) were retrieved while 15 (6%) were rejected. The statistical tools used for analyzing data were correlation and multiple regression techniques. Findings were that covid’19 pandemic negatively affected rural land transport business. The study concludes that the coronavirus pandemic caused a contraction in transport business. It is therefore recommended that, there is need for government to relax the stringent covid’19 protocols to allow economic activities to resume again. Campaigns on safety and hygiene should be intensified so that the populace will imbibe the culture of general cleanliness and personal hygiene amongst others.